ANALISIS HISTORIOGRAFI ATAS PEMIKIRAN AHMAD SYAFII MAARIF: Kajian Teoritik Vis A Vis Islam dan Pancasila - Saepulah, Asep (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article specifically discusses Ahmad Syafii Maarif's thoughts on Islam and Pancasila. More specifically, he wrote his thoughts in a Ph.D thesis entitled Islam as the Basis of State: A Study of the Islamic Political Ideas as Reflected in the Constituent Assembly Debates in Indonesia which has presented intellectual, historical and thought aspects that highlight between the Islamic group and the National Group in determining the philosophy of the Indonesian state. What is more important is that the sources used by Ahmad Syafii Maarif in this thesis are very varied. From articles, books, newspapers, news magazines, interviews to sources that have not been published in the original language. It seems that this is the first thesis on Islam and Pancasila which is quite comprehensive in the study related to Islam and state matters in Indonesia. The type of research in this article is library research with primary data in the form of the original work of Ahmad Syafii Maarif and secondary data as research support. Through this method, it is hoped that it can provide answers to questions related to Ahmad Syafii Maarif's historiography in the theoretical study of Islam vis a vis Pancasila. In conclusion, it can be seen how far the contribution of Ahmad Syafii Maarif's thoughts in dialectics the historiography of Islam and Pancasila as the basis of the state[Artikel ini secara khusus membahas pemikiran Ahmad Syafii Maarif tentang Islam dan Pancasila. Secara lebih spesifik pemikirannya itu dia tuliskan dalam sebuah tesis Ph.D-nya berjudul Islam as the Basis of State: A Study of the Islamic Political Ideas as Reflected in the Constituent Assembly Debates in Indonesia yang telah menyajikan aspek intelektual, sejarah dan pemikiran yang mengetengahkan antara kelompok Islam dan Kelompok Nasional dalam menententukan falsafat negara Indonesia. Yang lebih penting lagi adalah sumber yang digunakan Ahmad Syafii Maarif dalam tesis tersebut sangat bervariatif. Dari mulai artikel, buku, surat kabar, majalah berita,wawancara hingga sumber-sumber yang belum diterbitkan dalam bahasa aslinya. Tampaknya inilah tesis pertama tentang Islam dan Pancasila yang cukup komprehensif dalam pengkajian yang berhubungan dengan Islam dan masalah kenegaraan di Indonesia. Tujuan tulisan ini adalah mendeskripsikan sekaligus menganalisis metode, metodologi, teori, pemikiran hingga pendekatan yang digunakan oleh Syafii Maarif dalam tesisnya tersebut. Analisis historis menjadi metode yang digunakan Syafii Maarif. Karya Ahmad Syafii Maarif ini memberikan konstribusi besar kepada literatur dan menjadi inspirasi bagi peminat dan penulis sejarah Islam dan Pancasila, serta mampu menyumbangkan bangunan keilmuan Islam yang segar, adil dan lestari di Nusantara.]